The Role of Professional Codes in Regarding Ethical Conduct - Higgs-Kleyn, Nicola (Journal of business ethics, 1999)
This paper investigates the regulation of ethical behavior of professionals. Ethical perceptions of South African professionals operating in the business community (specifically accountants, lawyers and engineers) concerning their need for and awareness of professional codes, and the frequency and acceptability of peer contravention of such codes were sought. The existence of conflict between corporate codes and professional codes was also investigated. Results, based on 217 replies, indicated that the professionals believe that codes are necessary and are relatively aware of the contents of such codes. Despite these ethical tendencies, respondents (particularly lawyers) believe that their peers contravene their professional codes relatively often. No significant differences in ethical tendencies between professionals consulting to and those working in business were found. Many respondents were regulated by more than one code of ethics, but few experienced conflict between such codes. In the events of conflict occurring professionals chose to adhere to their professional code above others.